Assessing public participatory mechanisms in the water and sanitation sector in the Eastern Cape province of South Africa - Chibota, Runyararo (Department of Information Systems, 2019)
Public participation is considered fundamental in the management of water and sanitation. In the view of the South African government public participation is pivotal to addressing service delivery challenges in the country. However, despite investment in various participatory mechanisms, there is some reluctance from rural citizens to engage with municipalities. According to the National Policy Framework for Public Participation 2007, public participation is meant to be an “open, accountable process through which individuals and groups within selected communities can exchange views and influence decision-making. It is further defined as a democratic process of engaging people, deciding, planning, and playing an active part in the development and operation of services that affect their lives”. Thus, resistance by rural citizens to working collaboratively with the municipalities defeats the purpose of the public participation process. Preliminary literature reveals a dearth of research into the cause of the lack of interest in the public participation process from citizens. Existing literature indicates that there is dissatisfaction in the way the public participation process is being conducted, and that more examination is needed. The paucity of research is what triggered the author’s decision to analyse the participatory mechanisms being used by municipalities in the water and sanitation sector of the Eastern Cape. The study was, therefore, an assessment of participatory mechanisms and takes into account the perspectives of rural citizens whose views are thus stakeholder views. The objective was to determine the possible reasons for the dissatisfaction with the process in order to identify the factors that could be taken into account to improve the public participation process in the Eastern Cape. The main research question was: What are the South African rural publics’ perceptions on whether the participatory mechanisms used in the water and sanitation sector achieve the intended goals of public participation? The study assessed the participatory mechanisms used in the water and sanitation sector in the rural communities in South Africa. Two local municipalities in the province of Eastern Cape were used as a case study. Rural citizens’ perspectives on various participatory mechanisms were explored to establish if the mechanisms used are promoting the intended outcomes of public participation.